2021
DOI: 10.3389/fphar.2021.702152
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Release Syndrome Is an Independent Risk Factor Associated With Platelet Transfusion Refractoriness After CAR-T Therapy for Relapsed/Refractory Acute Lymphoblastic Leukemia

Abstract: Background: Chimeric antigen receptor T cell (CAR-T) therapy is successful in improving treatment outcomes for relapsed/refractory acute lymphoblastic leukemia (R/R ALL). However, toxicities associated with CAR-T therapy are being increasingly identified. Pancytopenia is one of the most common complications after CAR-T therapy, and platelet transfusions are an essential part of its supportive care.Study Design and Methods: This study aimed to assess the effectiveness of platelet transfusions for R/R ALL patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…One RCT was reclassified as NRSI and another one was classified as an ongoing RCT and was not still included because of its preliminary status only providing immature data for its primary outcome. 28 Therefore, two RCTs 29 , 30 and nine NRSI (two quasi-experimental studies 31 , 32 and seven cohort studies) 33 39 assessing the use of CAR-T in 1221 participants with B-cell lymphoma or T or B-cell acute lymphoblastic leukemia were included in the review. A detailed list with reasons for exclusion is presented in Supplemental Appendix 2 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One RCT was reclassified as NRSI and another one was classified as an ongoing RCT and was not still included because of its preliminary status only providing immature data for its primary outcome. 28 Therefore, two RCTs 29 , 30 and nine NRSI (two quasi-experimental studies 31 , 32 and seven cohort studies) 33 39 assessing the use of CAR-T in 1221 participants with B-cell lymphoma or T or B-cell acute lymphoblastic leukemia were included in the review. A detailed list with reasons for exclusion is presented in Supplemental Appendix 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, five cohort studies also reported incidence of CRS, ranging from 5% to 15% in the CAR-T groups 33 , 35 , 37 39 None of the above studies but Wang et al 39 provided explicit information on the incidence of CRS in their comparator groups, being assumed as zero events for these arms. We did not rate the certainty of evidence for this outcome due to insufficient information for the assessment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations